2018
DOI: 10.1016/j.jcmg.2016.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Low-Flow Severe Aortic Stenosis in Small-Body Patients Undergoing TAVR

Abstract: Among Japanese small-body patients with severe AS, both paradoxical LF and LF-LG severe AS were associated with poor outcomes following TAVR. SVi was an independent predictor of cardiovascular mortality after TAVR. (Optimised Transcatheter Valvular Intervention registry [OCEAN-TAVI]; UMIN000020423).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 29 publications
1
25
1
Order By: Relevance
“…Prior reports showed that pre-TAVI SVi is a powerful independent predictor of all-cause or cardiovascular mortality, and SVi is a better predictor of a left ventricular ejection fraction prognosis in patients with severe AS 3 15–17. The present study showed that post-TAVI SVi, not pre-TAVI, is an independent predictor of cardiovascular mortality and rehospitalisation for heart failure.…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations
“…Prior reports showed that pre-TAVI SVi is a powerful independent predictor of all-cause or cardiovascular mortality, and SVi is a better predictor of a left ventricular ejection fraction prognosis in patients with severe AS 3 15–17. The present study showed that post-TAVI SVi, not pre-TAVI, is an independent predictor of cardiovascular mortality and rehospitalisation for heart failure.…”
Section: Discussionsupporting
confidence: 46%
“…Low-gradient severe aortic stenosis (AS), which is classified into classical low-flow, paradoxical low-flow and normal-flow low-gradient AS, is associated with a higher mortality rate even after transcatheter aortic valve implantation (TAVI) than high-gradient severe AS 1 2. Our data also showed that a low-flow status was an independent predictor of cardiovascular mortality after TAVI 3. However, it has not yet been examined whether post-TAVI flow status affects the prognosis, especially in patients with low-gradient severe AS.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…Since malnutrition is associated with poor outcomes (Barr & Schumacher, 2003), and malnutrition might consequently relate to decreased QOL or mortality because of frailty syndrome, we also collected the following data on known predictors of poor outcomes in QOL and mortality post-TAVR (Arnold et al, 2014;Carreras et al, 2018;Hermiller, 2016;Kataoka, 2018;Puls et al, 2014;Reynolds, 2011;Schoenenberger et al, 2013;Shimura, 2017;Tribouilloy et al, 2015): disease information (classification of the New York Heart Association; left ventricular ejection fraction, %; mean pressure gradient [mean PG]: ≤40.0 mm Hg, severe; aortic valve area [AVA]: ≤1.0 cm 2 , severe; peak flow velocity [V max ]: ≤4.0 m/s, severe), diagnosed LF-LG AS (Hachicha, Dumesnil, Bogaty, & Pibarot, 2007), mortality risk score using the Society of Thoracic Surgeons score (high risk: ≤10%), physical function status (5-m gait speed, sec/5 m), basic activities of daily living (ADL) and the Katz Index of Independence in ADL (Shelkey & Wallace, 2000), frailty status (Clinical Frailty Scale [CFS]; frailty: ≥5) (Rockwood et al, 2005), and cognitive functional status (Mini-Mental State Examination [MMSE]; normal, ≥24) (Mitchell, 2009). These assessment tools have widely confirmed reliability and validity.…”
Section: Follow-up Participants At 1 Pom N = 56mentioning
confidence: 99%